Secondary pneumonia in tetanus patients: a review of six selectedcases (Case Report) (Faculty of Medicine Universitas Indonesia, 2005)
Tetanus, an infection by C.tetani continues to be a major health problem in the developing world. The course of the disease is typically prolonged, requiring weeks to months of supportive management to resolve. Several studies have been conducted to determine which factor/s really influenced the outcome of tetanus. Factors such as severity of spasms, age, sedation and tachycardia were found to significantly influence mortality. Patients now surviving the initial acute phase of their illness, but new problems have emerged autonomic dysfunction and hospital acquired pneumonia (often with multiresistant organisms) are now the commonest causes of death. This serial cases report presents six selected cases of tetanus, three patients acquired secondary pneumonia during treatment, among the three, two patients are elderly age 70 and 72 years old. Both of the presented patients died during treatment in the hospital. (Med J Indones 2005; 14: 117-21) Keywords : tetanus, pneumonia complication